Structural Design of a Timber Altar for the International Eucharistic Congress, Bombay (India), 1964 - Masani, N. J. (Indian Forester, 1965)
Line-drawing designs from qualified architects in India were invited by the Organising Committee of XXXVIII International Eucharistic Conllress held in Bombay in November-December, 1964, for open competition, in which Shri Suraj P. Subherwal, B. Arch., A.I.I.A., a young Architect of Calcutta, won the first prize. After the competition, Shri Subherwal was requested to adjust his designs to the full requirements including the design lay-out of the site (Plate I, fill. 3). His line-drawing concept was accepted by the. authorities for erection of the Main Altar structure. On this line diagram basis of the Architect, the author was approached for a possible and practical Timber structural design to be executed and guided at site of erection. This paper explains the main ideas of design, load data, timber choice and fabrication and erection technique so as to make an interesting and educative reading material for architects,. engineers, builders and the public at large.